Gestión administrativa y su incidencia en la calidad de los servicios al cliente del almacén ¨visto bueno stickers¨ cantón Quevedo 2012 - Uchuari Quezada, Daniel Augusto (2012)
"Approval Stickers" is a company that registers an existence since 2008 under the ruc 1103028161001, based in the province of Los Ríos. Quevedo Canton. Factors in the administration that affect the quality of customer service of the store "approval Stickers", which the company lacks and that were identified are: Kindness, responsiveness, personal appearance, attention and retention problems or suggestions. The general objective of the research applied to warehouse "approval Stickers" is to present a quality manual customer service. Periodically based on the operating procedures of quality customer service personnel perform monitoring, will jointly undertake a range of manual and improve the image of the infrastructure ¨ ¨ Having Good Stickers which will ensure its faithful implementation in each of the functions satisfying customer needs and the company can retain customers thereby generating profitability